THE EFFECTIVENESS OF USING COLLABORATIVE WRITING METHOD TO INCREASE STUDENTS' WRITING ABILITY IN SMPN 7 BANDUNG(A QUASI-EXPERIMENTAL RESEARCH IN THE SECOND GRADE STUDENTS OF SMPN 7 BANDUNG) - Lintang Kusuma, - (2009)
This paper was aimed at investigating whether there is significant difference between group that used collaborative writing method and group that did not use this method, and examining students' perceptions towards the use of this method. This quantitative research was conducted to the second grade of SMPN 7 Bandung through quasi-experimental design, and two classes (VIII.A and VIII.B) were chosen as samples. Furthermore, the data were collected by administering writing test and questionnaire. As results, the significant value did not exceed the level of significance (0.000 < 0.05), and there was significant difference between post-test means for experimental group (80.24) and control group (73.57). Thus, it was revealed that there was significant difference between group that used this method and group that did not use this method. Besides, the results of questionnaire showed that there were students' positive perceptions. Finally, it is concluded that this method is effective in increasing students' writing ability in SMPN 7 Bandung.